The Role of Nurses in Hypertension Management at Community Health Centers - Ampugo, Yaser Arivudin; Rayanti, Rosiana Eva; Natawirarindry, Catherine (Care : Jurnal Ilmiah Ilmu Kesehatan, 2024)
Hypertension is the most prevalent disease in Salatiga City, Central Java. Nurses play a crucial role in treating and preventing hypertension. However, no studies have specifically measured the role of nurses in Community Health Centers (Puskesmas). This study aims to describe the role of nurses in hypertension management at Community Health Centers. A qualitative case study was conducted at the Cebongan Health Center in Salatiga City between May and July 2023. Data were collected through in-depth interviews and observations involving 13 nurses who met the inclusion criteria. Triangulation was conducted by gathering additional input from community health center heads and cadres. Thematic analysis was applied to analyze the data, including transcription, coding, categorization, theme development, and drawing conclusions. Nurses at the Cebongan Health Center manage hypertension through various roles, including case finding via blood pressure screenings, acting as educators and consultants, coordinating care, and serving as role models for healthy living behaviors. However, challenges such as the limited number of nurses relative to the target area's population, inadequate infrastructure, and minimal community participation hinder efforts to control hypertension effectively in community health centers. While the role of nurses in managing hypertension has been implemented, it still requires optimization—particularly in areas like case finding through screenings and serving as role models for healthy living.